Impacts of climate change on organized sport: A scoping review - Orr, M.; Inoue, Y.; Seymour, R.; Dingle, G. (WIREs Climate Change, 2022)
The relationship between sport and the environment has been primarily examined to understand how sport impacts the natural environment. However, as the influence of climate change has become more apparent, there is a need to establish a systematic understanding of the impacts of climate change on the operations of sport. The aim of this review is to take stock of existing literature on climate change's impacts on organized competitive sport entities, with further attention paid to their adaptation efforts. A scoping review was conducted to identify relevant studies published between 1995 and 2021. After evaluating more than 2100 publications, we retained 57 articles and analyzed them to answer the research questions: (1) What evidence is available regarding the impacts of climate change on the operation of organized competitive sport entities? (2) What is known from the literature about the measures taken by organized competitive sport entities to adapt to the impacts of climate change? Our analysis yielded five major themes: (1) Heat impacts on athlete and spectator health; (2) heat impacts on athlete performance; (3) adaptive measures taken in sport; (4) suitability of various cities for event hosting; and (5) benchmarking and boundary conditions. This review reveals that there is evidence of some climate change impacts on sport, but the literature reflects only a small share of the global sport sector. Equally, much remains to be understood about the nature of adaptation.